2019
DOI: 10.33321/cdi.2019.43.13
|View full text |Cite
|
Sign up to set email alerts
|

Australian Gonococcal Surveillance Programme Annual Report, 2017

Abstract: The Australian Gonococcal Surveillance Programme (AGSP) has continuously monitored antimicrobial resistance in clinical isolates of Neisseria gonorrhoeae from all states and territories since 1981. In 2017, there were 7,835 clinical isolates of gonococci from public and private sector sources tested for in vitro antimicrobial susceptibility by standardised methods. Current treatment recommendations for gonorrhoea for the majority of Australia, is a dual therapeutic strategy of ceftriaxone and azithromycin. Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
53
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 14 publications
4
53
1
Order By: Relevance
“…The four most commonly supplied antibiotics in Australia are amoxicillin (35%), cephalexin (19%), roxithromycin (6%) and doxycycline (6%), together accounting for 66% of supplied antibiotics 29. Current patterns of antimicrobial resistance in gonococcal isolates in Australia28 suggest that most of these antibiotics would not be particularly effective at reducing oropharyngeal carriage of gonococci, except perhaps cephalexin. Furthermore, a recent trial of doxycycline postexposure prophylaxis in MSM suggested that doxycycline does not prevent gonorrhoea 30…”
Section: Discussionmentioning
confidence: 99%
“…The four most commonly supplied antibiotics in Australia are amoxicillin (35%), cephalexin (19%), roxithromycin (6%) and doxycycline (6%), together accounting for 66% of supplied antibiotics 29. Current patterns of antimicrobial resistance in gonococcal isolates in Australia28 suggest that most of these antibiotics would not be particularly effective at reducing oropharyngeal carriage of gonococci, except perhaps cephalexin. Furthermore, a recent trial of doxycycline postexposure prophylaxis in MSM suggested that doxycycline does not prevent gonorrhoea 30…”
Section: Discussionmentioning
confidence: 99%
“…Australia monitors the quality of their antimicrobial resistance data by providing an ongoing external quality assurance programme17 that was found to have an overall error rate of 3.1% over a 9-year period 18. The Indian Gonococcal Antimicrobial Surveillance Programme External Quality Assurance schemes for disc diffusion (2001–2007) found an overall interpretation concordance of 82% for five antibiotics and six participating laboratories 19…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of MenB disease is changing in Australia; its overall incidence has remained stable, but increased numbers of infections by serogroups W and Y since 2013 3 , 26 means that it accounted for 65% of IMD cases with a known serogroup during 2015, down from 83% during 2006–2014. There is also some regional variation; while incidence has declined in the three most populous states, the rate in the Northern Territory has been more variable, and has increased in South Australia, where it prompted the initiation of a large comparative study of MenB vaccination of adolescents in 2017 27…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the first large scale application of the multicomponent MenB vaccine in the UK, 25 proprietary laboratory assays predicted protection against 76% of MenB strains that cause disease in Australia 28 . Uncertainty remains as to whether this will prove to be optimistic, given marked changes in serogroup and subtype prevalence, 3 , 29 , 30 or whether the vaccine will provide protection beyond the B serotype, potentially including MenW, which could mean that its overall protective effect has been underestimated. Vaccine safety considerations are also paramount in individual risk–benefit assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation